2021
DOI: 10.2166/wst.2021.623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different D-amino acids on biofilm formation of mixed microorganisms

Abstract: This study aimed to determine the effects of D-tyrosine, D-aspartic acid, D-tryptophan and D-leucine on biofilm formation of mixed microorganisms. Results showed that, in the attachment stage, D-amino acids caused significant reduction in adhesion efficiency of mixed microorganisms to membrane surface. Moreover, D-amino acids have a promoting effect on the reversible adhesion of mixed microorganisms. The addition of D-amino acid generally inhibited the biofilm biomass, of which D-tyrosine has the best inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The effect was greatest against B. subtilis; however, the mechanism of action remains elusive and is considered unrelated to bacterial hydrophobicity or surface charge. Su et al, 172 using an "activated sludge" containing many kinds of bacteria and protozoa, demonstrated that D-Tyr, D-Asp, D-Trp, and D-Leu independently led to a significant reduction in cell adhesion efficiency while also increasing desorption efficiency to a flat membrane surface composed of polyvinylidene fluoride. Xu and Liu 173 also reported the significant surface inhibitory effects of D-Tyr on activated sludge adhesion when investigated on glass and polypropylene slides.…”
Section: Bacterial Adhesion Biofilm Formation and Dispersal At The Or...mentioning
confidence: 99%
See 3 more Smart Citations
“…The effect was greatest against B. subtilis; however, the mechanism of action remains elusive and is considered unrelated to bacterial hydrophobicity or surface charge. Su et al, 172 using an "activated sludge" containing many kinds of bacteria and protozoa, demonstrated that D-Tyr, D-Asp, D-Trp, and D-Leu independently led to a significant reduction in cell adhesion efficiency while also increasing desorption efficiency to a flat membrane surface composed of polyvinylidene fluoride. Xu and Liu 173 also reported the significant surface inhibitory effects of D-Tyr on activated sludge adhesion when investigated on glass and polypropylene slides.…”
Section: Bacterial Adhesion Biofilm Formation and Dispersal At The Or...mentioning
confidence: 99%
“…• Peptidoglycan component 68,121 • Modulation of peptidoglycan structure and synthesis 215 • Anti-germination properties to bacterial spores 136 • Provides cell wall resistance to protease activity 68,121 • Hypothesized role in nociception in bone cancer 308 • High levels associated with diseases of aging, primarily deposits in bone, skin, arteries, and lenses • Potential anticancer properties through the induction of cytotoxic H 2 O 2 synthesis of D-AA oxidase 309 • Association of high levels with gastric cancer 305,306 • Association of high levels with kidney disease and impaired renal function 313,314 D-Arginine • Modulation of bacterial virulence 174 • Eukaryotic cell protection from cell death in bacterial infections 174 D-Aspartic Acid • Protection from bactericidal agents (e.g., vancomycin) as a terminal residue of stem peptides 108,112,[124][125][126][127] • Inhibition of bacterial adhesion to abiotic surfaces 172 • Inhibition of biofilm formation 198,229 • Inhibition of planktonic MRSA growth 198 • Inhibition of metabolic activity 198 • Inhibition of bacterial growth 229 • D-Asp-NMDA receptor expression associated with osteoblast and osteoclast activity in vitro 300 • Regulation of collagen type I, osteocalcin, and alkaline phosphatase levels in osteoblasts 301 Increased levels in Paget's disease and osteoporosis 302 • Hypothesized association with oxidative stress and aging disorders, with deposits mainly found in bone, skin, arteries, and lenses 299 • Neurotransmission 297…”
Section: D-alaninementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, research has revealed that Cys has the potential to influence gut flora, possibly impacting the production of hydrogen sulfide (H 2 S; Hsu et al, 2022). Moreover, various d ‐amino acids have been found to restrict the growth of microbial biofilms, with d ‐tryptophan being identified as the most effective among them (Su et al, 2022). d ‐Aspartic acid is associated with the production of bodily hormones (Melville et al, 2017) and has been found to suppress inflammation by inhibiting cellular pyroptosis (Du et al, 2022).…”
Section: Introductionmentioning
confidence: 99%